Komunikasi Terapeutik Dokter dalam Penyembuhan Pengguna Narkoba di Badan Narkotika Nasional Provinsi Sumatera Utara - Hutabarat, Maria H. Enjelina; Vita, Nadra Ideyani; Riadi, Selamat (Universitas Medan Area, 2024)
This study was based on the increasing prevalence of drug use. The National Narcotics Agency (BNN) seeks rescue through rehabilitation, divided into inpatient and outpatient. At the North Sumatra Provincial Narcotics Agency (BNNP Sumut), outpatient is used to guide drug users to be aware and responsible. Therapeutic communication is the main method in BNN's outpatient rehabilitation. This study aims to explore the experience of doctors in assisting the recovery of drug users in BNNP North Sumatra and their communication process in healing. The qualitative descriptive method was used with 7 informants from doctors and counselors of BNNP Sumut. Data were collected through observation and interviews. Doctors identify factors that trigger drug use, both external (friends, family) and internal (family problems). This is the basis for the therapeutic communication approach in accompanying clients. The client's recovery process goes through the stages of therapeutic communication, starting from pre-interaction, orientation, work, to termination.